Efektivitas Program Berbasis Sekolah untuk Meningkatkan Resiliensi Mental Anak-anak Wilayah Konflik Timur Tengah - M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Nurzahara Sihombing (STIKes Ibnu Sina Ajibarang, 2025)
This research evaluates the effectiveness of school-based mental resilience programs for children in conflict zones of the Middle East based on the results of 47 studies (N=12,873 students) published between 2010 and 2023. The analysis reveals a significant increase in mental resilience scores (d=0.76, 95% CI [0.68, 0.84], p<.001) following the implementation of intervention programs for children in these conflict areas. Furthermore, multilevel regression analysis confirms that programs integrating psychosocial support factors into academic activities for children in conflict zones exhibit the strongest criterion effects (β=0.62, p<.001), followed by trauma-based interventions (β=0.58, p<.001) and coping skills training (β=0.51, p<.001). Additionally, the outcomes from interventions lasting more than six months demonstrate a greater criterion effect (d=0.82) than short-term programs (d=0.65). A 12-month follow-up indicates the sustainability of the intervention effects (d=0.69). These findings expand upon previous research by Forsberg & Schultz (2015) and Betancourt et al. (2008), which primarily focused on short-term interventions, successfully identifying effective long-term components of programs for children in conflict zones of the Middle East. Moreover, in contrast to the study by Gomez et al. (2017), which found the effectiveness of interventions limited to trauma-based programs, this research reveals that an integrated approach has a greater impact on specific subjects. Ultimately, this study provides the first empirical evidence testing the effectiveness of a sustainable school-based mental resilience intervention for children in conflict zones on a broader Middle Eastern scale.